Assessing the potential for multi-functional “hybrid” porous Al-phase change material structures - Kennedy, Andrew R. (Elsevier, 2016)
This study reports the potential for porous aluminium structures, containing porosity in the region of 50–80%, to provide enhancement of the rate of energy capture in phase change materials, whilst being capable of providing a basic mechanical function. The energy stored and the time for thermal exchange between warm water (at 65 °C) and porous aluminium, pure PCM and an Al-PCM hybrid structure was measured. It was observed that the melting of the PCM within the hybrid structure can be greatly accelerated by the continuous, porous aluminium structure. The energy uptake per second was found to follow an approximately linear dependence on the thermal effusivity for the material. This knowledge was used to predict the potential for enhancement of the rate of energy capture, by varying the porosity in the structure, whilst also estimating the detriment to the energy storage density and the mechanical strength. Appreciating this trade off in performance and properties is vital to the design of multi-functional porous structures.